The threat of persistence antimicrobial resistance on global food animal production: an essential role of poultry farmers and veterinarians to avoid the inevitable - Aliyu, Abdulrasheed Bello; Abdul Aziz, Saleha; Abu, Jalila; Zakaria, Zunita (Faculty of Veterinary Medicine, Universiti Putra Malaysia, 2013)
Antimicrobial agents are essential tool in treatment, control and prevention of infectious diseases that have devastating effects on animal health and welfare, sustainable livestock production in addition to the control of animal infections that could be passed on to humans (Marshall et al., 2011). According to the US National Research Council and Institute of Medicine states, “The benefit to human health in the proper use of antibiotics in food animals is related to the ability for these drugs to combat infectious bacteria that can be transferred to humans by either direct contact with the sick animal, consumption of food contaminated with pathogens from animals, or proliferation into the environment” (FDA, 2012). However imprudent use of these agents can lead to “the ability of microorganisms to survive or even grow in the presence of a given concentration of an antimicrobial agent, that is usually sufficient to inhibit or kill microorganism of the same species” and this phenomenon is termed as antimicrobial resistance (Anonymous, 2003), thus rendering the agents incapacitated to perform the above mention essential functions and hence may be a problem of global magnitude.